آثار مهارة الاستماع والقراءة على مهارة الكتابة لدى الطالبات بمعهد النّور دارالنجاح الثامنة جيدوكوم - Azizy, Rahmatika Nur; Susiawati, Wati; Muttaqin, Zainal; Raswan, Raswan (Kalimatuna: Journal of Arabic Research, 2023)
The aim of this research is to find out whether the skills of listening and reading Arabic texts possessed by female students at the Islamic boarding school have an influence on their ability to write Arabic. After the researchers conducted quantitative research, using data collection techniques in the form of tests, observation and documentation. The results obtained were that the influence of listening skills on writing had a calculated r value (0.513) greater than r table (with a value of 0.216) with a significance of 5%, so it was stated that listening skills had a medium level influence on writing skills. Meanwhile, regarding the influence of reading skills on writing, it is stated that rcount (with a value of 0.385) is slightly greater than rtable (with a value of 0.216) with a significance of 5%, so it is stated that writing skills have a weak level of influence on writing skills.